Odontalgus dongbaiensis sp. n. from eastern China, and a world catalog of Odontalgini (Coleoptera: Staphylinidae: Pselaphinae) - Yin, Zi-Wei; Newton, Alfred F.; Zhao, Tie-Xiong (Zootaxa, 2016)
Odontalgus dongbaiensis Yin and Zhao, new species is described from the eastern Chinese province of Zhejiang. This represents the first record of the tribe Odontalgini Jeannel, 1949 in China. The habitus, foveal pattern, and major diagnostic characters of the new species are illustrated, and the new species is diagnosed and compared with related congeners. A catalog of the world genera and species of Odontalgini is provided, with a full bibliography of the original descriptions and synonyms. Data on the type locality, type depository, and world distribution of each species are given. Odontalgus gracilides Newton, new replacement name, is proposed for O. gracilis Jeannel, 1964, which is a primary junior homonym of O. gracilis Raffray, 1904. Odontalgus vespertinus rhodesiae Jeannel, 1951 is synonymized with O. vespertinus Raffray, 1877, new synonym. Odontalgus rugulosus Jeannel, 1957 is selected as the correct original spelling of this species. Currently the Odontalgini contains fifty-six species and three subspecies grouped in five genera, with a disjunct distribution in the Afrotropical and Oriental regions, Korea, Japan, and Australia.